Verification of Structured Processes: A Method Based on an Unsoundness Profile - Roa, Jorge (2013)
The verification of business processes has been widely studied in the last two decades achieving significant results. Despite this, existing verification techniques based on state space exploration suffer, for large processes, the state space explosion problem. New techniques improved verification performance by structuring processes as trees. However, they do not support complex constructs for advanced synchronization and exception management. To cope with this issue we propose the definition of an unsoundness profile of a given process language, which specifies all possible combinations of control flow constructs that can lead to errors in the behavior of structured processes defined with such a language. In addition, we introduce the sequential and hierarchical soundness properties, which make use of this profile to determine soundness of a structured process with complex constructs in polynomial time. As an example, we defined an unsoundness profile for a subset of the BPMN language and verified the behavior of a BPMN process model.